AI-BASED TRAINING TO ENHANCE TEACHERS' BEHAVIORAL INTENTIONS AND WILLINGNESS TO UTILIZE AI TECHNOLOGY IN CLASSROOM LEARNING - Ranuharja, Fadhli; Willyansyah, Willyansyah; Marta, Rizka Yani; Hendra, Ayu; Rudi Mulya; Novid, Igor (Jurnal Empowerment, 2025)
The technological transformation in educational media has driven significant changes in teaching and learning processes, particularly highlighted by the COVID-19 pandemic, which underscored the importance of adopting Artificial Intelligence (AI) as an assistive tool in developing more effective online learning materials. This community service program was conducted in collaboration with SMAN 3 Padang Panjang, involving 22 teachers from grades X to XII as participants. The program was designed in three main phases: (1) preparation and field observation, (2) field implementation, and (3) evaluation. Evaluation results indicate that teachers demonstrate high behavioral intention and willingness to use AI in their teaching practices. The average scores on the behavioral intention aspect suggest that teachers are inclined to recommend and intend to use AI in the future, while on the willingness-to-use aspect, teachers are willing to dedicate time to learning and overcoming challenges related to AI usage. These findings suggest that AI-based training is effective in enhancing teachers' readiness and commitment to integrating technology into the teaching process, thereby potentially strengthening educational quality in the digital era